Peran Mediasi Customer Satisfaction Dalam Hubungan Antara Brand Image dan Customer Loyalty dengan Brand Love Sebagai Variabel Moderasi - Howardi Visza Adha; Wiry Utami (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyse the effect of brand image on customer loyalty with customer satisfaction as a mediating variable. In addition, this study also examines the role of a moderating variable in strengthening the relationship with customer loyalty. The research was conducted on coffee shop customers using a quantitative approach through the distribution of questionnaires to respondents who had purchased and experienced consuming products at the research object. The research data were analysed using the Structural Equation Modelling (SEM) method based on Partial Least Square (PLS). The results of the study indicate that brand image does not directly affect customer loyalty. These findings suggest that customer loyalty is not solely formed by brand image, but is also influenced by the experiences and satisfaction perceived by customers. On the other hand, brand image was proven to have a positive effect on customer satisfaction. This indicates that the better the company’s brand image, the higher the level of customer satisfaction. The study also found that customer satisfaction has a positive effect on customer loyalty, meaning that satisfied customers tend to have the intention to repurchase and maintain relationships with the company. Furthermore, customer satisfaction was proven to mediate the relationship between brand image and customer loyalty. However, the moderating variable used in this study was unable to provide a significant effect on customer loyalty. This study implies that companies need to focus more on improving customer satisfaction as the main strategy for building sustainable customer loyalty.